Characterization of the gassy sediment layer in shallow water using an acoustical method: Lake Kinneret as a case study. (12th August 2022) - Katsnelson, Boris; Uzhansky, Ernst; Lunkov, Andrey; Ostrovsky, Ilia
Abstract: Remote characterization and parameterization of gassy sediments have significant environmental importance for quantifying the global methane budget and assessing its impact on climate change. Acoustic techniques that have been developed hold advantages over direct sediment sampling (e.g., using pressurized and frozen cores), as they permit comparatively quick and cost‐effective assessments over the large bottom areas. This paper proposes a non‐invasive acoustic method that allows simultaneous assessments of the free gas content ( Θ ) and the thickness ( d ) of a gassy layer in the aquatic surface sediments. The method is based on amplitude measurements and frequency analysis of the bottom reflection coefficient in the wide frequency band (300–3500 Hz). The spatial variability of Θ and d in freshwater Lake Kinneret (Israel) is studied, where the upper sedimentary layer is characterized by a high organic matter content, high methane production rates, and a large Θ . The assessed values of Θ and d varied from 0.1% to 0.6%, and from 20 to 40 cm, respectively, depending on the location of measurements. These results are in reasonable agreement with gas void fractions measured directly in frozen sediment cores, where the depth‐averaged Θ varied from 0.4 % to 1.3 % . The suggested methodology should have considerable practical implementation for remote spatiotemporal monitoring of shallow gassy sediments in aquatic ecosystems.